A re-description of Cyrtodactylus chrysopylos Bauer (Squamata: Gekkonidae) with comments on the adaptive significance of orange coloration in hatchlings and descriptions of two new species from eastern Myanmar (Burma) - Grismer, L. Lee; Wood, Perry L., Jr.; Thura, Myint Kyaw; Win, Nay Myo; Grismer, Marta S.; Trueblood, Llyod A.; Quah, Evan S. H. (Zootaxa, 2018)
The karstic foothills and hilly western edge of the Shan Plateau of eastern Myanmar continue to be sources of discovery for new species of the gekkonid genus Cyrtodactylus. Two new karst-associated species within this unique landscape from Mandalay Region—C. aunglini sp. nov. from the Kyauk Nagar Cave and C. myaleiktaung sp. nov. from Mya Leik Taung Mountain—are described on the basis of color pattern, morphology, and genetics. A molecular phylogeny of the C. gansi group (defined herein) based on 1481 base pairs of the mitochondrial gene ND2 and its flanking tRNAs place C. aunglini sp. nov. as the sister species to C. gansi and C. myaleiktaung sp. nov. as the sister species of C. chrysopylos. A new population of C. chrysopylos from a boulder-strewn, karstic ridge near the village of Yane, Shan State at an elevation 951 m is reported here. Genetic and geographic variation as well as differences in natural history between it and the lowland cave population of C. chrysopylos from the type locality in the Panlaung-Pyadalin Cave Wildlife Sanctuary, Shan State at 303 m are discussed. Hatchlings of the new population from Yane are nearly uniformly bright-orange in color. We provide evidence in support of a hypothesis claiming this color functions as a mechanism for crypsis during low levels of illumination and is not involved in intraspecific communication.